Clinical Predictors of Hospital-acquired Pneumonia Associated with Acute Ischemic - Alexis Suárez Quesada; Ezequiel López Espinosa; Noelsis García Verdecia; Miguel Ángel Serra Valdés (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Background: hospital-acquired pneumonia is a constant challenge given the current microbiological spectrum, antimicrobial resistance together with its high mortality, morbidity and hospital costs. Objective: to identify the clinical predictors of pneumonia associated with acute ischemic stroke. Methods: a prospective cohort study was conducted in 201 patients diagnosed with acute ischemic stroke consecutively admitted to the stroke unit of the General Carlos Manuel de Céspedes Teaching Hospital during the first seven days after the onset, from January 2012 through December 2013. The independent predictors of hospital-acquired pneumonia were obtained using multivariable logistic regression. Results: fifty six point seven percent were male. The mean age was 64.17 ± 14.33 years. Cases of hospital-acquired pneumonia associated with stroke accounted for 19, 9 %. Subjects who developed pneumonia were older (68.55 ± 13.51 vs. 63.08 ± 14.36 years), had a lower score in the Glasgow Coma Scale (8.00 ± 2.60 vs. 14.00 ± 2.82), and an increased number of leukocytes at admission (10.888 ± 3.487 vs. 9.233 ± 2.539 × 109/L). The following independent factors were identified: Glasgow Coma Scale ≤ 11 (OR: 26.099; 95 % CI 7.164-85.075), history of chronic obstructive pulmonary disease (OR: 8.896; 95 % CI 1.203-65.779), dysphagia (OR: 7.652; 95 % CI 2.369- 24.720), history of heart failure (OR: 4.583; 95 % CI 1.240- 16.932) and dysarthria/severe motor aphasia (OR: 4.222; 95 % CI 1.374- 12.975). Conclusions: the resulting logistic regression model is valid for predicting post-stroke pneumonia based on data routinely acquired.